Membrane‐initiated estrogen signaling in prostate cancer: A route to epithelial‐to‐mesenchymal transition. Issue 11 (14th August 2019) - Gadkar, Sushama; Nair, Shardool; Patil, Smita; Kalamani, Shilpa; Bandivdekar, Atmaram; Patel, Vainav; Chaudhari, Uddhav; Sachdeva, Geetanjali
Abstract: The plasma membrane (PM) is considered as a major druggable site. More than 50% of the existing drugs target PM proteins. In the wake of emerging data indicating a key role of estrogens in prostate cancer (PCa) pathogenesis, the study was undertaken to explore whether the estrogen binding sites exist on the PM and if such sites are functionally relevant in PCa. Estradiol (E2) binding to the PM was detected in androgen‐dependent (LNCaP), androgen‐independent (PC3, DU145) PCa cell lines, nontumorigenic (RWPE1) prostate epithelial cell line, and rat prostate cells. Conventional estrogen receptors (nuclear estrogen receptors), known for their nuclear localization, were detected in the PM enriched extracts. This was indirectly confirmed by reduced localization of ERs on the PM of cells, silenced for the expression of their cognate genes. Further, unlike cell‐permeable E2, stimulation with cell‐impermeable estradiol (E2‐BSA) did not induce proliferation in LNCaP cells. However, stimulation with E2‐BSA led to alterations in the phosphorylation status of several kinases including GSK3 and AKT, along with the hyperphosphorylation of cytoskeletal proteins such as β‐actin and cytokeratin 8 in LNCaP. This was accompanied by epithelial‐to‐mesenchymal (EMT) features such as increased migration and invasion; higher vimentin expression, and a concomitant decrease in the E‐cadherin expression. These effects were not observed in RWPE1 cells. Interestingly, cell‐permeable E2 failed to induce EMT in PCa cells. This in vitro study is the first to suggest that the PM‐initiated estrogen signaling contributes to higher invasiveness in PCa cells. Plasma membrane ERs may act as novel targets for PCa therapeutics.